Transformation dynamics of the natural cover in the dry chaco ecoregion: a plot level geo-database from 1976 to 2012 - Vallejos, M., Volante, J.N., Mosciaro, M.J., Vale, L.M., Bustamante, M.L. and Paruelo, J.M. (My University, 2015)
The aim of this work was to characterize the spatial and temporal dynamics of the transformation of the natural cover in the Dry Chaco ecoregion from 1976 to 2012. Dry forests in this region have one of the highest deforestation rates in the world. We analyzed 44 Landsat scenes, including part of Argentina, Paraguay and Bolivia. The analysis was based on tracking individual transformed plots of the entire Dry Chaco region for over more than three decades using the same protocol. Until the end of 2012 15.8 million ha of the original habitats of the Chaco were transformed into croplands or pastures. Our study showed that the greater annual rates of transformation were observed in Paraguay, where deforestation increased dramatically in the last decade, reaching values higher than 4.0% in 2010, the highest historical value in the entire region. The size of the transformed plots increased significantly through the studied period both in Argentina and Paraguay, while in Bolivia decreased. At the landscape level, the use of several fragmentation indices showed the disruption of the continuity and connectivity of the original vegetation. The spatially explicit description of the dynamics of transformed areas is an indispensable tool for natural resources management, territorial planning and deforestation impacts assessment. Highlights •We generated a geo-database of the natural cover transformation in Dry Chaco. •We analyzed the deforestation patterns at plot and landscape level. •The transformed area in Dry Chaco by the end of 2012 totalized 15.8 million ha. •Annual Rates of Transformation were intensified from 1976 to 2012 at country level. •Paraguay showed an exponential increase in the Annual Rate of Transformation.
Keywords: Deforestation, Geodatabase, Monitoring, Land use change, Annual rate of forest change